Bolsa Família (Family Grant) Programme: an analysis of Brazilian income transfer programme - Luciana Mourão; Anderson Macedo de Jesus (Field Actions Science Reports, 2012)
Income transfer programmes are common in various countries and play an important role in combating poverty. This article presents a review of the results of the Bolsa Família (Family Grant) Programme, implemented in Brazil by the government of Lula da Silva in 2004. Over the last seven years many evaluations of the programme have been conducted, allowing an overview of its results and its strong and weak points to be mapped. Five central aspects relating to the programme are discussed in article five: (1) programme access, (2) hunger fighting results, (3) programme financial impacts, (4) conditioning factors of education and health, (5) supplementary programs and social mobility. The results of scientific research were presented for each of these aspects, and any of these believed to be convergent or divergent were discussed. As a general result it was concluded that the programme has generated significant results for the country, but there are still some issues that need to be reviewed, such as conditioning factors and the integrated management of the programme.